Development of an Environmentally Friendly Larvicidal Formulation Based on Essential Oil Compound Blend to Control Aedes aegypti Larvae: Correlations between Physicochemical Properties and Insecticidal Activity - Lucia, Alejandro (2020)
Oil in water (o/w) emulsions stabilized by an amphiphilic copolymer have been studied in relation to their potential insecticidal activity against Aedes aegypti mosquito larvae. These emulsions contain as oil phase different blends of two isomeric essential oil compounds, thymol and carvacrol. The results show that the addition of carvacrol facilitates the dispersion of the oil within the aqueous phase, with the stabilization and polydispersity of the emulsions being controlled by the change of the ratio between the copolymer concentration and that of the oil phase (Rcop/EOC). Emulsions containing pure essential oil compounds as oil phase do not present any significant difference on their larvicidal activity against mosquito larvae, with emulsions containing only thymol being slightly more effective than those containing only carvacrol as oil phase. Furthermore, the use of blendscontaining different weight fractions of thymol and carvacrol as oil phase results in formulations with an additive larvicidal activity in relation to those with the pure compounds. Despite the larvicidal activity of the emulsions, they do not provoke inhibition to the emergence of adult individuals in Aedes aegypti populations. The spreading and evaporation of the emulsions onto solid surface, which may be an important parameter for the performance of larvicidal formulations, was found to be dependent on the same parameters that govern the stability of the emulsions. This study helps on seeking new alternatives for the preparation of new eco-sustainable formulations against insect pest.